PENGARUH KONSENTRASI ECO-ENZYME TERHADAP INTENSITAS SERANGAN FUSARIUM OXYSPORUM PADA TANAMAN CABAI (Capsicum annuum L.) - SARNI, SARNI; SYAIR, SYAIR; HISEIN, WAODE SITI ANIMA; TAUFIK, MUHAMMAD; ARSYAD, MIRZA ARSIATY; PAKKI, TERRY; ASNIAH, ASNIAH; ULFA, NUR ISNAINI (Jurnal Agroteknos, 2023)
Red chili (Capsicum annuum L.) is a vegetable commodity that is widely consumed by Indonesian people, both as a food flavoring and for nutritional fulfillment. one of the reasons for the lack of maximum chili production is caused by fusarium wilt. This study aims to determine the effect of eco-enzyme concentrations on the intensity of F. oxysporum attack on chili plants. This research was arranged using a randomized block design (RBD) in which there were 6 treatments and 4 replications. The treatments were P0 : No treatment (Control), P1 : 1 mL Eco-enzyme/500 mL distilled water, P2 : 1 mL Eco-enzyme/750 mL distilled water, P3 : 1 mL Eco-enzyme/1000 mL distilled water, P4 : 1 mL Eco-enzyme/1250 mL distilled water, and 1 mL Eco-enzyme/1500 mL distilled water. The research variables were plant height, number of leaves, time of appearance of fusarium wilt symptoms, and intensity of fusarium wilt attack. The results showed that the treatment of 1 mL of eco-enzyme/1500 mL of distilled water on the intensity of disease attacks showed that at 10 weeks MST the lowest attack intensity was 1,54%.